FACTORS RELATED TO SOLID MEDICAL WASTE HANDLING MANAGEMENT AT TEUKU UMAR HOSPITAL, CALANG ACEH JAYA REGENCY - Rinaldi, Alfian; Mawardi, Mawardi; Akbar, Fahrisal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Factors related to the implementation of medical waste management at General Hospital (RSU) are Hospital Policy, Human Resources (HR), Funds, Technical Guidelines, Facilities, and Infrastructure. Among these five factors, human resources and infrastructure are the most important factors to achieve hospital waste management objectives. Reliable human resources are needed and the infrastructure used must comply the requirements in the Decree of the Minister of Health the Republic of Indonesia No. 1204/Menkes/SK/X/ 2004. The research aims to determine the relationship between hospital policies and the handling of medical waste at Teuku Umar Hospital. Method: Type of analytical survey research with a Cross Sectional approach. The research sample was 30 employees of the sanitation section of Teuku Umar Hospital, Calang Aceh Jaya Regency. Data collection techniques used questionnaires and data analysis using the chi square test. Results: The research results showed a relationship between hospital policies (p-value=0.001), human resources (HR) (p-value=0.001), infrastructure (p-value=0.001), funds (p-value=0.001), technical guidelines (p-value=0.001), and the handling of medical waste (p-value=0.001) at the Teuku Umar Hospital, Calang Aceh Jaya Regency. Recommendation: It is hoped that hospitals will improve the quality of human resources in the medical waste handling department, therefore the medical waste can be handled properly.